Guidelines for Drafting Liability Neutral Transportation Engineering Documents and Communication Strategies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
In the legal system, transportation engineering documents drafted by the transportation industry include manuals, studies, research documents, memoranda, and email. These documents are frequently used by litigants and courts as evidence bearing on the standard of care or duties for transportation agencies sued for alleged negligence in operation of transportation facilities.The TRB National Cooperative Highway Research Program's NCHRP Legal Research Digest 83: Guidelines for Drafting Liability Neutral Transportation Engineering Documents and Communication Strategies contains a writing guide for technical and non-technical authors and those employees who interact with the public and the media. This digest will assist authors in avoiding concepts and language that have legal implications by promoting clear, direct, objective, and fact-based expression.
Keywords: Transportation and Infrastructure

Communication Strategies for Building Confidence in COVID-19 Vaccines: Addressing Variants and Childhood Vaccinations - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The fourth wave of the COVID-19 pandemic in the United States has been fueled by the delta variant, which is more contagious than earlier variants, and a slowing down in new vaccinations. Most hospitalizations and deaths in the United States are occurring among people who are not vaccinated. This context affirms the importance of tackling vaccine hesitancy and communicating with parents of children who are eligible to be vaccinated and those for whom future eligibility is anticipated. This rapid expert consultation identifies actionable guidance that state and local decision makers can use to communicate with the public to build confidence in and promote the uptake of COVID-19 vaccines. This rapid expert consultation was produced through the Societal Experts Action Network (SEAN), an activity of the National Academies of Sciences, Engineering, and Medicine that is sponsored by the National Science Foundation and the Alfred P. Sloan Foundation. SEAN links researchers in the social, behavioral, and economic sciences with decision makers to respond to policy questions arising from the COVID-19 pandemic. This project is affiliated with the National Academies' Standing Committee on Emerging Infectious Diseases and 21st Century Health Threats and the Standing Committee on Advancing Science Communication.
Keywords: Health and Medicine

Communication Strategies for Airport Passenger Access and Mobility - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Access to relevant, precise, and timely information is crucial for a pleasant experience in air travel. Travelers with cognitive and sensory disabilities, aging travelers, and travelers with limited English proficiency need alternative approaches to those provided for general travelers for accessing and communicating air travel information.The TRB Airport Cooperative Research Program's ACRP Synthesis 101: Communication Strategies for Airport Passenger Access and Mobility details how airports and airlines are leading the way in developing new and creative services to provide information and thus enhance passenger access and mobility.Among the report's findings are the following. Airports’ current efforts to improve passenger access and mobility follow three key trends: commitment to seamless customer experience, development of a sense of place at airports, and improvement of efficiency and personalized service using technology such as biometrics, robotics, and artificial intelligence.
Keywords: Transportation and Infrastructure

Health Literacy and Communication Strategies in Oncology: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Health literacy is a critical skill for engaging in healthy behaviors to reduce disease risk and improve health outcomes across the continuum of cancer care. However, estimates suggest that more than one-third of the U.S. adult population has low health literacy, and nearly half of all patients with cancer have difficulty understanding information about their disease or treatment. Low health literacy among patients with cancer is associated with poor health and treatment outcomes, including lower adherence to treatment, higher rates of missed appointments, and an increased risk of hospitalization. Low health literacy can also impede informed decision making, especially as cancer care becomes increasingly complex and as patients and their families take more active roles in treatment decisions. To examine opportunities to improve communication across the cancer care continuum, the National Cancer Policy Forum collaborated with the Roundtable on Health Literacy to host a workshop, Health Literacy and Communication Strategies in Oncology, July 15-16, 2019, in Washington, DC. Patients, patient advocates, clinicians, and researchers, representatives of health care organizations, academic medical centers, insurers, and federal agencies explored the challenges of achieving effective communication in cancer care. This publication summarizes the presentations and discussions of the workshop.
Keywords: Health and Medicine

Speaking of Health: Assessing Health Communication Strategies for Diverse Populations - Institute of Medicine (The National Academies Press, 2002)
We are what we eat. That old expression seems particularly poignant every time we have our blood drawn for a routine physical to check our cholesterol levels. And, it's not just what we eat that affects our health. Whole ranges of behaviors ultimately make a difference in how we feel and how we maintain our health. Lifestyle choices have enormous impact on our health and well being. But, how do we communicate the language of good health so that it is uniformly received-and accepted-by people from different cultures and backgrounds?
Keywords: Health and Medicine

A Guidebook for Successful Communication, Cooperation, and Coordination Strategies Between Transportation Agencies and Tribal Communities - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2011)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 690: A Guidebook for Successful Communication, Cooperation, and Coordination Strategies Between Transportation Agencies and Tribal Communities includes guidelines designed to help departments of transportation and tribal communities work together to achieve successful transportation projects on tribal lands.The report explores a wide range of issues and topics to be considered and offers a flexible approach that can be adapted to most situations. The report also includes case studies to illustrate successful practices.The report on the project that led to the development of NCHRP Report 690 was published as NCHRP Web-Only Document 171.
Keywords: Transportation and Infrastructure

Business Case and Communications Strategies for State DOT Resilience Efforts (The National Academies Press, 2023)
As transportation agencies face an increasing frequency and magnitude of risks, strategies and tools are essential for demonstrating, communicating, and gaining support for integrating resilience into transportation decisions and investments. NCHRP Web Only Document 385: Business Case and Communications Strategies for State DOT Resilience Efforts, from TRB's National Cooperative Highway Research Program, provides state departments of transportation (DOTs) and other transportation organizations resources to help explain the value of investing in resilience.
Keywords: Transportation and Infrastructure

Strategies for Building Confidence in the COVID-19 Vaccines - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Ensuring strong demand for and promoting acceptance of the COVID-19 vaccines is critical to achieving herd immunity, protecting the most vulnerable populations, and reopening social and economic life. People who are hesitant, reluctant, distrusting, or otherwise not motivated with respect to being vaccinated need resources, information, and support for making the vaccination decision that is right for them. Public engagement and effective communication through clear, transparent messaging will play a central role in building confidence in the COVID-19 vaccines. This rapid expert consultation describes a variety of public engagement and communication strategies that can be implemented at the national, state, and local levels to change patterns of interaction with the public, address hesitancy about the vaccines, and build trust. This rapid expert consultation was produced through the Societal Experts Action Network (SEAN), an activity of the National Academies of Sciences, Engineering, and Medicine that is sponsored by the National Science Foundation. SEAN links researchers in the social, behavioral, and economic sciences with decision makers to respond to policy questions arising from the COVID-19 pandemic. This project is affiliated with the National Academies' Standing Committee on Emerging Infectious Diseases and 21st Century Health Threats.
Keywords: Health and Medicine

Exploring the Science on Measures of Body Composition, Body Fat Distribution, and Obesity: Proceedings of a Workshop Series - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
The National Academies Roundtable on Obesity Solutions hosted a public workshop series in April and June 2023 that explored the current science on measures of body composition and body fat distribution. Discussions focused on the strengths and limitations, and clinical and anthropological perspectives of body mass index (BMI) as a measure of adiposity and health. Presentations also shed light on the connection between misinformation and bias and stigma, as well as challenged current communication strategies to improve messaging about obesity.
Keywords: Food and Nutrition

Encouraging Adoption of Protective Behaviors to Mitigate the Spread of COVID-19: Strategies for Behavior Change - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
This rapid expert consultation is intended to help decision makers identify strategies for increasing adherence to protective behaviors that can mitigate the spread of COVID-19. Ultimately, the focus is on increasing knowledge, reducing barriers, and emphasizing efforts that make healthier choices easier and rewarding, to complement communication interventions. It was produced through the Societal Experts Action Network (SEAN), an activity of the National Academies of Sciences, Engineering, and Medicine that is sponsored by the National Science Foundation. SEAN links researchers in the social, behavioral, and economic sciences with decision makers to respond to policy questions arising from the COVID-19 pandemic.
Keywords: Health and Medicine

Encouraging Protective COVID-19 Behaviors among College Students - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Developmental psychology and brain research can support campus leaders as they work together with students to prevent the spread of COVID-19 on college campuses and in the surrounding communities. This rapid expert consultation presents research-informed habit-promoting and communication strategies to encourage the adoption of behaviors that can stem the spread of COVID infections on college campuses. The Societal Experts Action Network (SEAN) is an activity of the National Academies of Sciences, Engineering, and Medicine that is sponsored by the National Science Foundation. SEAN links researchers in the social, behavioral, and economic sciences with decision makers to respond to policy questions arising from the COVID-19 pandemic. This project is affiliated with the National Academies' Standing Committee on Emerging Infectious Diseases and 21st Century Health Threats.
Keywords: Health and Medicine

Building Trust in Public Health Emergency Preparedness and Response (PHEPR) Science: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
On March 29-30, 2022, the National Academies of Sciences, Engineering, and Medicine hosted a workshop aimed at examining the roles of trust and trustworthiness in the public health emergency and response (PHEPR) science enterprise - the institutions, the research process, and the researchers and practitioners - across the continuum of pre-event, event, response, and mitigation. The first day examined issues of trust in PHEPR science, where they originate, and what can be done to build and maintain trust in public health agencies. The second day shifted discussions to communication and strategies to address misinformation and ensure clear understanding of public health communications. The final session allowed workshop participants and public attendees - through an interactive Miro board session - to reflect on workshop discussions and share strategies to build public trust over the next 5 years. This Proceedings of a Workshop-in Brief summarizes the presentations and discussions that occurred at the workshop.
Keywords: Health and Medicine

2020 Census Data Products: Demographic and Housing Characteristics File: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
This proceedings summarizes the presentations and discussions at the Workshop on the 2020 Census Demographic and Housing Characteristics File, held June 21-22, 2022. The workshop was convened by the Committee on National Statistics of the National Academies of Sciences, Engineering, and Medicine to assist the U.S. Census Bureau with its new disclosure avoidance system for 2020 Census data products, which implements algorithms providing differential privacy. The workshop focused specifically on the Demographic and Housing Characteristics File, a major source of data for local governments, particularly those with small populations, and many other data users in the federal, state, academic, and business sectors. The intent was to garner feedback from users on the usability of the privacy-protected data by evaluating DHC demonstration files produced with the proposed TopDown Algorithm on 2010 Census data.
Keywords: Behavioral and Social Sciences

The Critical Public Health Value of Vaccines: Tackling Issues of Access and Hesitancy: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Immunization against disease is among the most successful global health efforts of the modern era, and substantial gains in vaccination coverage rates have been achieved worldwide. However, that progress has stagnated in recent years, leaving an estimated 20 million children worldwide either undervaccinated or completely unvaccinated. The determinants of vaccination uptake are complex, mutable, and context specific. A primary driver is vaccine hesitancy - defined as a "delay in acceptance or refusal of vaccines despite availability of vaccination services". The majority of vaccine-hesitant people fall somewhere on a spectrum from vaccine acceptance to vaccine denial. Vaccine uptake is also hampered by socioeconomic or structural barriers to access. On August 17-20, 2020, the Forum on Microbial Threats at the National Academies of Sciences, Engineering, and Medicine held a 4-day virtual workshop titled The Critical Public Health Value of Vaccines: Tackling Issues of Access and Hesitancy. The workshop focused on two main areas (vaccine access and vaccine confidence) and gave particular consideration to health systems, research opportunities, communication strategies, and policies that could be considered to address access, perception, attitudes, and behaviors toward vaccination. This publication summarizes the presentations and discussion of the workshop.
Keywords: Health and Medicine

Space Radiation and Astronaut Health: Managing and Communicating Cancer Risks - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Astronauts face unique health-related risks during crewed space missions, and longer-duration missions that extend to greater distances in our solar system (including to the Moon and Mars) will likely increase those risks. Cancer risks due to ionizing radiation exposure are one of these health-related risks. Assessing, managing, and communicating radiation-induced cancer risks associated with spaceflight are challenging because of incomplete knowledge of the radiation environment in space, limited data on radiation-induced cellular damage mechanisms, lack of direct observations from epidemiological studies, and the complexities of understanding radiation risk. At the request of the National Aeronautics and Space Administration (NASA), an ad hoc committee of the National Academies of Sciences, Engineering, and Medicine convened to provide advice on NASA's proposed updates to their space radiation health standard, which sets the allowable limit of space radiation exposure throughout the course of an astronaut's career. Space Radiation and Astronaut Health: Managing and Communicating Cancer Risks provides the committee's recommendations and conclusions regarding the updated space radiation health standard, NASA's radiation risk communication strategies, and a process for developing an ethics-informed waiver protocol for long-duration spaceflight missions.
Keywords: Environment and Environmental Studies; Health and Medicine

Guidance for Diversity in Airport Business Contracting and Workforce Programs - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Many airports are already taking active steps to address and unlock the benefits of a diverse and inclusive workforce. These programs provide benefits to the airport and surrounding communities, but there has not been a comprehensive benefit-cost analysis for diversity contracting programs and their impact on the workforce.The TRB Airport Cooperative Research Program's ACRP Research Report 217: Guidance for Diversity in Airport Business Contracting and Workforce Programs provides guidelines to assist airport operators and various stakeholders at airports of all types and sizes to identify and quantify the benefits, costs, and regional economic impact of diversity contracting for airport businesses.As recipients of federal funds, airports are required to administer a federal program that seeks to provide equal access for participation in airport-related business opportunities. Likewise, many airports are also obligated to do so under state and local programs.The report includes additional materials: an Airport Diversity Contracting Tool and a Tool Users Guide.
Keywords: Transportation and Infrastructure

Flourishing in Adolescence: A Virtual Workshop: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Adolescence is a dynamic time for both brain development and social pressures, making it a critical period to understand mental, emotional, and behavioral health, yet it is often overlooked in terms of policies and service interventions, which makes many young people feel unheard when communicating their own challenges. To explore best practices in providing and supporting adolescent health services and key messaging and communication strategies related to the mental, emotional, and behavioral health of adolescents, the National Academies of Sciences, Engineering, and Medicine's Forum for Children's Well-Being held a workshop on May 5, 2020. The workshop featured a panel of youth representatives who shared their own experiences related to mental, emotional, and behavioral health. This publication summarizes the presentation and discussion of the workshop.
Keywords: Behavioral and Social Sciences

Year in Review 2023: Roundtable on Obesity Solutions - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
During 2023, the Roundtable on Obesity Solutions remained committed to reducing the prevalence of obesity by working across systems and sectors and maintaining a focus on structural racism, bias and stigma, and health communication. Framing their activities and discussions within these three areas, the roundtable and its five Innovation Collaboratives covered important and timely issues, including exploring the strengths and limitations of body mass index and other measures of body composition and body fat distribution, and strategies for improving communication about body weight. This annual report summarizes the activities of the roundtable in 2023.
Keywords: Food and Nutrition

Understanding How to Motivate Communities to Support and Ride Public Transportation - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2008)
TRB's Transit Cooperative Research Program (TCRP) Report 122: Understanding How to Motivate Communities to Support and Ride Public Transportation explores the methods and strategies used by public transportation agencies in the United States and Canada to enhance their public images and motivate the support and use of public transportation. The report identifies and describes methods and strategies used by other industries (comparable to public transportation) to enhance their public image and to motivate the support and use of their products and services. This report also examines the perceptions, misperceptions, and use of public transit, and the extent to which these affect support. Finally, the report identifies effective communication strategies, campaigns, and platforms for motivating individuals to action in support of public transportation, as well as ways to execute those communication strategies, campaigns, and platforms.
Keywords: Transportation and Infrastructure

Leveraging Health Communication, Data, and Innovative Approaches for Sustainable Systems-Wide Changes to Reduce the Prevalence of Obesity: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The Roundtable on Obesity Solutions of the Health and Medicine Division of the National Academies of Sciences, Engineering, and Medicine held a virtual public workshop, Leveraging Health Communication, Data, and Innovative Approaches for Sustainable Systems-Wide Changes to Reduce the Prevalence of Obesity, on June 22, 2021. The workshop, the second in a series of three workshops to examine foundational drivers of obesity and sustainable systems-wide changes to reduce the prevalence of obesity, explored strategies for leveraging health communication and data-informed, innovative approaches. Participants in the workshop discussed how health communication might enhance the understanding and the use of current modeling and data-driven efforts to advance obesity solutions; they also explored innovative data and policy approaches for obesity solutions. This Proceedings of a Workshop-in Brief highlights the presentations and discussions that occurred at the workshop.
Keywords: Food and Nutrition